O ser professor na pedagogia do sentido: identidade, saberes e práticas - Pereira, Aline Romana Alves (2024)
The Pedagogy of Meaning is inspired by the thoughts of Viktor Frankl, and has a prospective character, which means it is not tied to human conditioning but encourages individuals to look forward by searching for a meaning in life that sustains them, seeking to offer a free and responsible response to the questions asked by life. Since the pedagogical practice is permeated by knowledge, this research aims to understand how the teaching knowledge of Basic Education teachers who base their work on the Pedagogy of Meaning is structured. This conception of education (the Pedagogy of Meaning) is relatively new, and few works discuss it, both at a regional and national level. Therefore, more specifically, the interest of this work lies in the identification of pedagogical and didactic knowledge, based on an inventory of knowledge proposed by D’Ávila and Ferreira, which underlies the pedagogical practice of teachers, as well as the analysis of the constitution of teacher’s identity within the horizon of the Pedagogy of Meaning. This research is empirical, and its data collection was carried out through semi-structured interviews with teachers who have based their practices on Franklian anthropology for at least five years. As a data analysis method, Thematic Analysis was used from the perspective of Braun and Clarke. The results demonstrated that the teacher’s identity constitution, here subdivided into Teaching Identity and Teacher Role, has as its central axis the search for meaning, with the consequent promotion of the search for meaning in the lives of students and other educational actors. Pedagogical knowledge goes beyond the classroom and occurs both in the relationship with the student and in the relationship with different educational actors. This knowledge is revealed above all through the teacher's ethical stance through his freedom and responsibility for choosing his attitude in face of life’s inevitable situations. Didactic knowledge (specific teaching knowledge), subdivided into class mediation and discipline mediation (understood here as a curricular component), reveals the spiritual person. The class mediation knowledge covered in this work was a favorable environment for learning, interpersonal relationships, conflict management and an inclusive environment. In short, permeated by a humanized perspective, this knowledge focuses on encouraging the student’s self-transcendence and leads the teacher to consider the totality of each student. The discipline mediation knowledge covered in this work was the identification and overcoming of learning difficulties, planning, teaching, and evaluation methodologies. This knowledge is centered on the processes of searching, discovering, and making meaning through pedagogical practices. Thinking from noodynamics, this knowledge involves, for example, contextualizing the content within the student's reality and inserting an existential axis into the curricular content and evaluative dynamics, considering the student’s constant search for meaning. In particular, this work advances regarding existing works on the subject by discussing in depth the teacher’s identity constitution and listing and discussing an inventory of knowledge in their respective pedagogical practices. In this way, we believe we can contribute to the debate and help both those who do not yet know the Pedagogy of Meaning and those who wish to deepen their research.